New Advances and Illustrations in Applied Geochemistry - Gong, Qingjie; Shi, Zeming (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The ninth national conference on applied geochemistry in China will be held in Chengdu, hosted by the committee of applied geochemistry, Chinese Society for Mineralogy, Petrology and Geochemistry (CSMPG). In order to facilitate the academic exchange on applied geochemistry, this Special Issue is intended for the presentation of new advances and case illustrations in the field of applied geochemistry. The guest editors of this Special Issue are Dr. Gong, a professor from China University of Geosciences (Beijing), and Dr. Shi, a professor from the Chengdu University of Technology. This Special Issue was opened on 27 June 2022 and closed on 1 July 2023. A total 14 scientific papers have been published that capture various hot and challenging issues in applied geochemistry. These articles belong to three broad groups: (i) new advances and case illustrations in resource exploration which focus on exploration techniques in covered areas and anomaly determinations of geochemical survey data; (ii) new advances and case illustrations in environment assessment which focus on heavy metals of soils, soil nutrients assessment and geochemical survey of a top geoherb; and (iii) new advances in the basic theory of geochemistry such as elemental abundances of moon samples, equation of state of fluid mixtures, the formation's dynamic mechanism of a dendrite, provenance indices of geological materials, etc. In which, a promising concept, geochemical gene, was introduced and illustrated in tracing soils and determining geochemical anomalies.